To Sack or Not To Sack: The Impact of Managerial Change on Team Performance in English Premier League Football - Knibbs, Danielle Marie (2018)
Within the modern-day sports industry, the role of the football manager is under intense pressure and constant scrutiny by various stakeholders. More often than not, it is the manager who is held accountable for a string of bad match results and who is sacked correspondingly. The presently high managerial attrition rate is now accepted to be a part of the business. Although this unhealthy churn of football managers is well recognised, the effects that this leadership change has on performance remains unclear. The following study addresses this area of interest by examining the impacts that managerial change has on English Premier League performance. The analysis for this investigation uses game statistics (from seasons 2008/09 to 2017/18), in a paired-samples t-test, to measure the difference in points per match and league position before and after managerial change. The main findings from this study show that managerial change leads to an upturn in match performance, where both points per match and league position improve.